2006
DOI: 10.1242/dev.02621
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63 plays an anti-apoptotic role in ventral bladder development

Abstract: The bladder, the largest smooth-muscle organ in the human body, is responsible for urine storage and micturition. P63, a homolog of the p53 tumor-suppressor gene, is essential for the development of all stratified epithelia, including the bladder urothelium. The N-terminal truncated isoform of p63, ⌬Np63, is known to have anti-apoptotic characteristics. We have established that ⌬Np63 is not only the predominant isoform expressed throughout the bladder, but is also preferentially expressed in the ventral bladde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
81
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(87 citation statements)
references
References 52 publications
6
81
0
Order By: Relevance
“…In contrast, umbrella cells of the superficial layer display a distinct phenotype characterized by lack of p63 expression and presence of certain low molecular weight CKs, such as CK20 and CK18, as well as uroplakins [eg, uroplakin II (UPII) 19,20 ]. Our group and others previously found that p63 is essential for urothelial differentiation 21 and that p63-null mice developed a nontransitional default simple cubical epithelium. 22 In addition, Signoretti et al 23 reported that the urothelium of 18.5-day p63-null embryos contain a single layer that resembles umbrella cells and expresses uroplakin III (UPIII).…”
mentioning
confidence: 58%
“…In contrast, umbrella cells of the superficial layer display a distinct phenotype characterized by lack of p63 expression and presence of certain low molecular weight CKs, such as CK20 and CK18, as well as uroplakins [eg, uroplakin II (UPII) 19,20 ]. Our group and others previously found that p63 is essential for urothelial differentiation 21 and that p63-null mice developed a nontransitional default simple cubical epithelium. 22 In addition, Signoretti et al 23 reported that the urothelium of 18.5-day p63-null embryos contain a single layer that resembles umbrella cells and expresses uroplakin III (UPIII).…”
mentioning
confidence: 58%
“…Defects of the dorsal external genitalia include epispadias with urethral defects and various dorsal external genitalia anomalies with relatively low frequency (Jeffs, 1987). Birth defects affecting the bladder, such as bladder exstrophy with associated malformation of the urethra has been reported in 1 of about 30,000-50,000 births (Cheng et al, 2006;Jeffs, 1987). Affected children often require multiple reconstructive surgical procedures (Jeffs, 1987;Johnston, 1975), increasing the impetus for research into the developmental bases of normal and abnormal urogenital organogenesis.…”
Section: Research Articlementioning
confidence: 99%
“…Both TAp63 and ΔNp63 can be alternatively spliced at the 3′ terminus to produce α, β, and γ isoforms (11). ΔNp63 isoforms are selectively expressed at high levels in basal cell compartments of stratified and glandular epithelia, including in the bladder and prostate (12)(13)(14).…”
mentioning
confidence: 99%
“…Heterozygous p63 mutations underlie various human syndromes of ectodermal dysplasia, orofacial clefting, and limb malformation (15), and p63 KO mice show defects in limb, craniofacial, and epithelial development. These mice lack all stratified epithelia and their derivatives (i.e., mammary, lachrymal, and salivary glands), die at birth from dehydration, and have markedly abnormal prostate and bladder epithelia (12,13,16,17). Specific KO mice for the TA and the ΔNp63 isoforms reveal that these anomalies result from ΔNp63 absence (18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation